Form of Register in Buying and Selling Conversations at Dayun Market in Siak Regency - Endah Rahayu; Erni Erni (Indonesian Journal of EFL and Linguistics, 2023)
The community is not bound by rules when communicating and making buying and selling transactions. The use of registers occurs in various regions, one of which is in the Dayun District, Siak Regency. The research objective is to describe the form of register used by traders and buyers in the Dayun market. The method used in this study is content analysis. Data collection techniques include observation techniques, records, and notes. Data analysis is content analysis. The results showed that there were 16 closed-enclosed registers and 3 open registers. The language used in buying and selling transactions is more specific. This study concludes that the form of registers in buying and selling transactions at the Dayun market in Siak Regency generally uses the form of a limited enclosure with conversations using informal language and spontaneous conversations. The implications of the research results can be used in the development of language teaching materials about the diversity of register variations that develop in society. For the public, its function is to learn the peculiarities of buying and selling registers in a market.